A Clinicopathological Report of a 93-Year-Old Former Street Boxer With Coexistence of Chronic Traumatic Encephalopathy, Alzheimer's Disease, Dementia With Lewy Bodies, and Hippocampal Sclerosis With TDP-43 Pathology - Yang, Chunhui; Nag, Sukriti; Xing, Guoqiang; Aggarwal, Neelum T.; Schneider, Julie A. (Frontiers in Neurology, 2020)
Abstract Chronic Traumatic Encephalopathy (CTE) has recently been recognized as a new neurodegenerative tauopathy. The pathognomonic lesion of CTE consists of p-tau aggregates in neurons, astrocytes, and cell processes around small vessels in an irregular pattern at the depths of the cortical sulci. CTE is believed to be caused by a sequela of repeated mild traumatic brain injury (TBI). One of the CTE subtypes is the late onset of cognitive impairment. Here we reported a 93-year-old former street boxer who had a premortem history of Alzheimer’s disease (AD). However, autopsy examination showed mixed pathology of stage IV CTE, AD and neocortical type dementia with Lewy bodies. Currently, clear clinical diagnostic criteria for CTE have not been established. Therefore, it is valuable for clinicians to recognize that CTE can overlap with other neurodegenerative diseases.